PENGARUH LATIHAN BEANBAG RELAYTERHADAPKECEPATAN LARI JARAK PENDEK 100 METER PADAATLET ATLETIK PUTRA PPLP RIAU - Muhammad sukri sukri; Ramadi '; Kristi Agust Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrac, This research was conducted to find out whether there was an influence of beanbag relay exercises toward speed of 100 meters sprint on men  athelete athletic of PPLP Riau. The data  In this research was an  experimental, The  total number of athletes in this research  6 people. The Instruments which have done in this research was the  100 meter sprint speed test which was aims to measure  speed. Then, the data  processed with statistic,  to normalitas test with lilieforrs test on significan extent Alfa  = 0,05, the  hypothesis put forward there was  influence of beanbag relay exercise toward speed of 100 meters sprint on athlete athletic of  PPLP Riau.Based on the analysis  of the t test found the t obtain was 3.166 and t table 2.015 means t obtain > t table. Based on the mean score of  pre test was 6.64 test and the mean score of post test  was 6.83 and based  on t- test after calculated there was difference numbers  that increase or increasing with mean score  0.972. From the explanation above can be concluded, there was the influence of beanbag relay  exercise to ward  of  speed 100 meters  sprint on athlete athletics  PPLP Riau . Keywords         :           Beanbag Relay Excercise  Toward Speed of 100 Meters Sprint on Men  Athletes Athletic in PPLP Riau.